2009
DOI: 10.1158/1078-0432.ccr-08-1813
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Proteasome and HDAC Inhibitors for Uterine Cervical Cancer Treatment

Abstract: Purpose: Cervical cancer cells are addicted to the expression of the human papillomavirus (HPV) oncoproteins E6 and E7. The oncogencity of E6 is mediated in part by targeting p53 and PDZfamily tumor suppressor proteins for rapid proteasomal degradation, whereas the E7 oncoprotein acts in part by coopting histone deacetylases (HDAC)1/2. Here, we examine the hypothesis that inhibition of proteasome function and HDAC activity would synergistically and specifically trigger cervical cancer cell death by the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
74
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(79 citation statements)
references
References 49 publications
5
74
0
Order By: Relevance
“…Moreover, we show that the combination of HDACi with a proteasome inhibitor has a much higher efficacy, with respect to the treatment with HDACi alone, inducing the death of cell lines deriving from ATCs. In agreement with our findings, the synergism of proteasome inhibitors with HDACis has recently been reported in glioma, in cervical cancer and in leukemia (Miller et al, 2007(Miller et al, , 2009Dai et al, 2008;Yu et al, 2008;Lin et al, 2009), strongly supporting our molecular model and suggesting the application of this combined treatment in other types of cancers.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, we show that the combination of HDACi with a proteasome inhibitor has a much higher efficacy, with respect to the treatment with HDACi alone, inducing the death of cell lines deriving from ATCs. In agreement with our findings, the synergism of proteasome inhibitors with HDACis has recently been reported in glioma, in cervical cancer and in leukemia (Miller et al, 2007(Miller et al, , 2009Dai et al, 2008;Yu et al, 2008;Lin et al, 2009), strongly supporting our molecular model and suggesting the application of this combined treatment in other types of cancers.…”
Section: Discussionsupporting
confidence: 92%
“…(16,17) Recently, several reports showed that HDACs are strongly expressed in cancerous tissue, and the expression of class I HDACs is an independent prognostic marker in various cancers, such as ovarian, colorectal and cervical cancer. (32)(33)(34) The present study showed that HDAC1 ⁄ 2 were expressed in the nuclei of non-neoplastic epithelial cells and carcinoma cells in the gallbladder, although nuclear staining was slightly weaker in the former than in the latter. This pattern was verified in cultured normal epithelial and carcinoma cells, indicating that HDAC1 ⁄ 2 expression level is a little higher in cancerous tissue; however, its expression is not specific to carcinoma cells in the gallbladder.…”
Section: Ink4asupporting
confidence: 46%
“…In addition to DNA methylation, the role of histone marks and chromatin remodeling factors in viral and host genome alterations has prompted the in vitro investigation of the effects of epigenetic drugs that target histone modification proteins, such as HDACs (Jiang et al, 2007;Lin et al, 2009). Furthermore, it has been proposed that the combination of epigenetic and conventional antiviral therapies, for example, unmasks HIV reservoirs and prevents the spread of the virus to uninfected CD4 þ T cells (Richman et al, 2009).…”
Section: Discussionmentioning
confidence: 99%